Paradigms, Paradigm Shifts and Classification - Gopinath, M. A. (Journal of Information and Knowledge, 1999)
Developments in scientific paradigms indicate growth of knowledge in different stages. Paradigm shifts indicate the landmarks in the growth of knowledge. A study of Aviation Systems Engineering and its correlations to the Dewey Decimal Classification are presented. The structure of knowledge classification have to indicate paradigm shifts.